Update on pathomechanisms and treatments in allergic rhinitis - Zhang, Yuan; Lan, Feng; Zhang, Luo (Allergy (Copenhagen), 2022)
Allergic rhinitis (AR) is a global health problem with increasing prevalence and association with an enormous medical and socioeconomic burden. New recognition of immune cells such as type 2 innate lymphocytes (ILC2s), T helper (Th2) 2 cells, follicular helper T cells, follicular regulatory T cells, regulatory T cells, B cells, dendritic cells, and epithelial cells in AR pathogenesis has been updated in this review paper. An in‐depth understanding of the mechanisms underlying AR will aid the identification of biomarkers associated with disease and ultimately provide valuable parameters critical to guide personalized targeted therapy. As the only etiological treatment option for AR, allergen‐specific immunotherapy (AIT) has attracted increasing attention, with evidence for effectiveness of AIT recently demonstrated in several randomized controlled trials and long‐term real‐life studies. The exploration of biologics as therapeutic options has only involved anti‐IgE and anti‐type 2 inflammatory agents; however, the cost‐effectiveness of these agents remains to be elucidated precisely. In the midst of the currently on‐going COVID‐19 pandemic, a global life‐threatening disease, although some studies have indicated that AR is not a risk factor for severity and mortality of COVID‐19, this needs to be confirmed in multi‐centre, real‐life studies of AR patients from different parts of the world.